Brain Interleukin-17A contributes to neuroinflammation and cardiac dysfunction in rats with myocardial infarction - Yu, Yang; Weiss, Robert M.; Wei, Shun-Guang (Frontiers in Neuroscience, 2022)
Proinflammatory cytokines produced outside the central nervous system can act in the brain to promote sympathetic activation that contributes to the progression of heart failure (HF). Interleukin (IL)-17A, a key inflammatory regulator which orchestrates immune responses to promote chronic inflammation, has been implicated in the pathophysiology of HF. We previously reported that IL-17A acts within the brain, particularly in the hypothalamic paraventricular nucleus (PVN), to increase expression of inflammatory mediators and, consequently, sympathetic outflow. The present study sought to determine whether IL-17A levels are elevated in a rat model of HF induced by myocardial infarction and, if so, whether increased expression of IL-17A in the brain itself contributes to neuroinflammation and cardiac dysfunction in this disease setting. Male SD rats underwent coronary artery ligation (CL) to induce HF or sham operation (Sham). Compared with Sham rats, HF rats exhibited significantly increased IL-17A levels in plasma, beginning within 1 week with a peak increase at 4 weeks after CL. IL-17A levels in cerebrospinal fluid (CSF) were also increased in HF rats and correlated with IL-17A levels in the plasma. The mRNA expression of IL-17A and its receptor IL-17RA, but not IL-17RC, was markedly upregulated in the PVN of HF when compared with Sham rats. Genetic knockdown of IL-17RA by bilateral PVN microinjections of an IL-17RA siRNA AAV virus attenuated mRNA expression of proinflammatory cytokines and chemokines, and ameliorated sympathetic activation and cardiac function in HF rats. These data indicate that elevated expression of IL-17A in the brain in HF contributes to the excessive central inflammatory state and cardiac dysfunction in HF. Interventions to suppress IL-17A/IL-17RA axis in the brain have the potential for treating HF.